Agenda for the nation - Aaron, Henry J.; Lindsay, James M., 1959-; Nivola, Pietro S. (Brookings Institution Press, 2003)
More powerful and affluent today than ever, the United States has promising opportunities to influence the course of history. Yet these prospects are shadowed by significant perils and burdens. In this visionary book, leading scholars from the Brookings Institution and other prominent research organizations and universities analyze the major domestic and foreign policy problems facing the nation over the next five to ten years. The challenges on the domestic front are formidable: assuring fair but affordable access to health care, shoring up retirement income for an aging population, encouragi.